VIDEO GAMES AND ESL/EFL: THE POSSIBILITY OF USING VIDEO GAMES AS AN EDUCATIONAL TOOL FOR CHILDREN PERSONAL LEARNING - Possumah, Hendrik Yohant (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2023)
This article discusses the possibility of using video game as an educational tool for children personal learning. Since the first video games were introduced in the 1970’s, people have been discussing both the negative and the positive effects of video games. Whereas most public address video games as the responsible party on degrading the academic grades and morale of children nowadays, people might have seemed to overlook the role that video games play in our lives by providing us with a medium to entertain ourselves. This article will first talk about a brief history of video games before continuing to discuss several opinions on video games. It will also look at the current discussions and debates regarding the use of video games as learning tools and education. This will then be followed by some concerns about the negative impact of video games as well as the reasons behind these concerns. It will then describe what aspects where video games can help ESL/EFL students in the personal learning, providing some examples in the process. Finally, some suggestions about how different interest groups can be involved to assist and maximize the use of video games for personal learning. It is my contention that video games can be a helpful tool for the ESL/EFL learners in their Personal Learning process at home.